FAKTOR RISIKO HIPERTENSI PADA REMAJA - Fira Mardianti; Dewi Rachmawati; Suprajitno Suprajitno (Jurnal Kesehatan Hesti Wira Sakti, 2022)
Introduction: hypertension can occur in adults and adolescents, many factors influence the occurrence of hypertension in adolescents. The purpose of this study was to determine the risk factors that can affect the occurrence of hypertension in adolescents. Methods: The research design is a traditional review, with literature sources from the google scholar database, with inclusion criteria for articles published in 2016-2020, which can be downloaded in their entirety, equipped with DOI or ISSN or E-ISSN and cross-sectional and case-control research designs. A search using the keyword risk factor "hypertension" found 21 articles and only 5 articles that matched the inclusion criteria, then the selected articles were presented in the form of tables and narratives. Results: Risk factors for hypertension include BMI, obesity, physical activity, family history of hypertension, gender, smoking habits, stress, and the habit of consuming excess salt or sodium. Conclusion: the dominant risk factors for hypertension often occur in adolescents due to risk factors for obesity, family history of hypertension, and physical activity. It is expected for adolescents to always maintain their health and fitness such as exercise and maintaining a good diet to prevent hypertension in adolescents and at health facilities, it is necessary to prevent hypertension in adolescents, one of which is through socialization